Thermally-induced nickelocene fragmentation and one-dimensional chain assembly on Au(111) - Divya Jyoti; Alex Fétida; Laurent Limot; Roberto Robles; Nicolás Lorente; Deung-Jang Choi (Communications Chemistry)
Abstract The ability to control molecular adsorption and transformation on surfaces is key to advancing nanoscale fabrication, catalysis, and quantum materials engineering. Transition-metal metallocenes, such as nickelocene (NiCp2), offer intriguing opportunities due to their well-defined electronic and magnetic properties, making them ideal candidates for studying surface interactions at the atomic level. We investigate the adsorption and transformation of NiCp2, a nickel atom coordinated by two cyclopentadienyl (Cp) rings, on a Au(111) surface using scanning tunneling microscopy (STM) and density functional theory (DFT) calculations. At low temperatures, NiCp2 preferentially adsorbs at herringbone elbows and step edges, forming ordered assemblies. Upon heating, NiCp2 molecules dissociate into NiCp complexes and Cp radicals. The NiCp fragments self-assemble into one-dimensional chains, which further arrange into triangular structures due to the underlying Au(111) substrate, while Cp radicals exhibit low diffusion barriers on the surface. The dissociated NiCp fragments are non-magnetic, contrasting with the magnetic properties of intact NiCp2 molecules. The formation of one type of dimer of the NiCp fragment is rendered possible by the stabilization granted by gold atoms. This study highlights the controlled formation and assembly of surface-confined nanostructures via temperature-driven molecular dissociation.